Organizational commitment by the type of employment contract: A case study of a higher education institution located in the Northeast Portugal - Ribeiro, Maria Isabel (2022)
Currently, higher education organizations face several challenges in trying to improve their organizational capacity, disseminate knowledge and encourage community service (Pucciarelli & Kaplan, 2016; Lesley, 2018; Kaplan & Haenlein, 2016). In this sense, the organizational commitment of employees can be decisive for the success of organizations since it is considered an important tool to achieve organizational goals. The present study aimed to determine the level of organizational commitment of employees of a Public Higher Education institution, located in the Northeast Portugal and to determine whether the type of employment contract is a differentiator factor of the organizational commitment. Therefore, a quantitative, observational and cross-sectional study was carried out based on the application of a questionnaire. Subsequently, 105 responses were obtained. The questionnaire included the scales of organizational commitment of the three-dimensional model developed by Meyer and Allen (1991). The results showed that the respondents' global commitment to the organization, in general, was moderate. Taking into account the three dimensions of the model, employees recorded higher levels of affective commitment, moderate levels of calculative commitment and lower levels of normative commitment. Additionally, it was found that the type of employment contract was different in only two of the three dimensions of the three-dimensional model of organizational commitment, namely, normative and calculative.